(untitled) (MAUSAM, 1980)
The severe cyclonic storm with a core of hurricane winds which struck the Andhra Pradesh coast on 12 May 1979, was tracked by radar from Madras over an unusually long range. The eye was seen at a range of 425 km which is a record for a radar on the Indian coasts. Even five days before landfall the radar gave indications of the likely northwesterly movement of the storm, a climatologically less probable direction. The extrapolation of the radar track also gave a good indication of point of landfall. These features facilitated timely warnings and effective precautionary measures. When the storm came close to coast radar detection was not so satisfactory possibly because of subnormal radio propagation conditions. As seen from radar data the storm had a small well-formed eye which widened out as it approached the coast. However heights of cloud tops in the eyewall the maximum rainfall rate in the eyewall and the areal rainfall in the core area remained fairly constant during the period in which they could be observed, suggesting that the storm remained of constant intensity for about 24 hours before land-fall. The observed surface winds and pressures also support this conclusion. The left sector of the eyewall was better developed and associated with intense rainfall. The system can as a whole be classed as a mature cyclone of small extent.